Super-resolution probe to monitor HNO levels in the endoplasmic reticulum of cells - Ali, Firoj; Sreedharan, Sreejesh; Ashoka, Anila Hoskere; Saeed, Hiwa K.; Smythe, Carl G. W.; Thomas, Jim A.; Das, Amitava (Analytical Chemistry, 2017)
Selective detection of nitroxyl (HNO), which has recently been identified as a reactive nitrogen species, is a challenging task. We report a BODIPY-based luminescence ON reagent for detection of HNO in aqueous solution and in live RAW 264.7 cells, based on the soft nucleophilicity of the phosphine oxide functionality toward HNO. The probe shows high selectivity to HNO over other reactive oxygen/nitrogen and sulfur species. Luminescence properties of the BODIPY-based chemodosimetric reagent make it an ideal candidate for use as a reagent for super-resolution structured illumination microscopy. The viability of the reagent for biological in vivo imaging application was also confirmed using Artemia as a model.

Tracking HOCl concentrations across cellular organelles in real time using a super resolution microscopy probe - Ali, Firoj; Aute, Sunil; Sreedharan, Sreejesh; Anila, H. A.; Saeed, Hiwa K.; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
BODIPY derivative, SF-1, exclusively shows a fluorescence ON response to HOCl and images endogenously generated HOCl in RAW 264.7 macrophages. Widefield and super resolution structured illumination microscopy images confirm localization in the Golgi complex and lysosomes, and hence specifically detects HOCl generated in these organelles. SF-1 is compatible with 3D-SIM imaging of individual cells.